To solve the equation \(x^2 + 2x = 3\), we can first rewrite it in standard form:
\[ x^2 + 2x - 3 = 0 \]
Next, we can factor this quadratic equation. We need to find two numbers that multiply to \(-3\) (the constant term) and add up to \(2\) (the coefficient of the linear term).
The factors of \(-3\) that meet these criteria are \(3\) and \(-1\). Therefore, we can factor the equation as follows:
\[ (x + 3)(x - 1) = 0 \]
Setting each factor to zero gives the solutions:
- \(x + 3 = 0 \quad \Rightarrow \quad x = -3\)
- \(x - 1 = 0 \quad \Rightarrow \quad x = 1\)
So, the solutions to the equation \(x^2 + 2x = 3\) are:
\[ x = -3 \quad \text{and} \quad x = 1 \]
Now we can summarize this in a response format:
Response: \( x = -3, 1 \) (or "x equals negative 3 comma 1")